Group Reputations, Stereotypes, and Cooperation in a Repeated Labor Market - Healy, Paul J (American Economic Review, 2007)
Reputation effects and other-regarding preferences have both been used to predict cooperative outcomes in markets with inefficient equilibria. Existing reputationbuilding models require either infinite time horizons or publicly observed identities, but cooperative outcomes have been observed in several moral hazard experiments with finite horizons and anonymous interactions. This paper introduces a full reputation equilibrium (FRE) with stereotyping (perceived type correlation) in which cooperation is predicted in early periods of a finitely repeated market with anonymous interactions. New experiments generate results in line with the FRE prediction, including final-period reversions to stage-game equilibrium and noncooperative play under unfavorable payoff parameters. (JEL C72, C73, C78, J41)